The evolution of consumer decision making: A bibliometric analysis and literature review - Narongrith, Titikorn; Yoopetch, Chanin (Edelweiss Applied Science and Technology, 2026)
This bibliometric review examines the evolution of consumer decision-making (CDM) research from 1987 to 2024, focusing specifically on the integration of artificial intelligence (AI) into consumer behavior research. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic analysis of 2,163 peer-reviewed articles from the Scopus database was conducted. To map the intellectual structure of the field, the VOSviewer software was used for comprehensive co-citation analysis, co-word analysis, and graphical network visualization. The results identified three distinct schools of thought: rational choice and behavioral economics, technology and digital systems adoption, and service quality evaluation. Furthermore, a significant paradigm shift from traditional psychological models toward AI-driven frameworks was observed, with the United States, the United Kingdom, and Germany leading global research output. Synthesizing these findings, this study proposes an adaptive-bounded rationality model as a critical conceptual direction for future research, confirming that AI has substantially redefined both theoretical and empirical approaches to understanding consumer behavior. Consequently, practitioners can leverage these insights to design consumer-centric marketing strategies utilizing predictive analytics while proactively addressing critical ethical concerns related to algorithmic transparency and consumer autonomy.